ISSUES OF PREPARING TEACHING AND METHODOLOGICAL MATERIALS IN THE SUBJECT OF "MATHEMATICS" IN PROFESSIONAL EDUCATIONAL INSTITUTIONS (Modern education and development, 2025)
The article discusses the reforms implemented in the system of professional education in Uzbekistan based on the subject "Mathematics", as well as the features of increasing students' interest in individual subjects, including mathematics. The article lists some developers and methods associated with the module.